(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2022)
This study focuses on oil and gas exploration in the South China Sea (SCS) from the period of the British North Borneo Company’s (BNBC) administration of North Borneo in 1881 until the introduction of the National Cabotage Policy (Malaysia) on 1st January 1980. The interesting history of Sabah’s oil and gas exploration needs to be revisited especially following the establishment of Petroliam Nasional Berhad or Petronas in 1974 which has enabled Sabah to be supplied with oil and gas resources produced from the offshore wells in 1980. This analysis relies heavily on primary sources in the form of official documents, reports and newspapers obtained from the Sabah State Archives (SSA), Malaysia. The study found that, although oil exploration of North Borneo or Sabah was initially carried out by BNBC since 1881, it was only strengthened after the end of the Japanese occupation. This development became more pronounced following the changes in the rule-based international system, notably the introduction of maritime law starting from the 1950s, which provided opportunities to both the British and Sabah governments through various companies, to conduct offshore oil exploration in the SCS. Oil exploration activities in the SCS area have proven to be lucrative, especially in terms of its contribution to the Malaysian economy. Kajian ini memfokuskan tentang eksplorasi minyak dan gas di Laut China Selatan (LCS) dari tahun 1881 ketika British North Borneo Company (BNBC) mentadbir Borneo Utara dan terbatas sehingga pengenalan Dasar Kabotaj Negara (Malaysia) pada 1 Januari 1980. Rentetan sejarah yang menarik berkenaan eksplorasi minyak dan gas Sabah perlu diamati semula khususnya setelah Petroliam Nasional Berhad atau Petronas ditubuhkan pada tahun 1974 yang membolehkan Sabah dibekalkan dengan sumber minyak dan gas yang dihasilkan dari telaga luar pantai Sabah pada tahun 1980. Kajian ini banyak bergantung kepada sumber primer dalam bentuk dokumen rasmi, laporan dan akhbar yang diperolehi dari Arkib Negeri Sabah (ANS), Malaysia. Kajian mendapati bahawa walaupun percubaan eksplorasi minyak Borneo Utara atau Sabah kemudiannya telah dilaksanakan oleh BNBC semenjak tahun 1881, kegiatan tersebut hanya diperkukuh selepas tamat tempoh pendudukan Jepun. Perkembangan ini semakin ketara apabila berlaku perubahan dalam sistem antarabangsa yang bersifat rule-based yakni pengenalan undang-undang kelautan bermula dari tahun 1950-an yang telah memberi peluang kepada British dan kerajaan Sabah, melalui pelbagai syarikat yang dilantik, untuk menjalankan eksplorasi minyak ke kawasan luar pantai di LCS. Kegiatan cari gali minyak sehingga ke kawasan LCS terbukti membuahkan hasil khususnya dalam memakmurkan ekonomi Malaysia.